Informasi Anomali Akrual dalam Pembentukan Portofolio Saham - Rowland Bismark Fernando Pasaribu (Jurnal Akuntansi dan Bisnis, 2010)
The accrual information is discussed in light with the multifactor asset pricing theory. It is argued that the capital market processes information efficiently, and that low accruals firms are risky and therefore earn higher average returns. In other words, the level of accruals proxies for the loading on a fundamental risk factor that drives stock returns. The objective of this study is to prove significance influence of accrual information and to evaluate the performance of stock portfolio constructed by Treynor Index, Jensen-Alpha, and Sharpe Index. The final sample are the past and present member of LQ-45 public companies. Following Fama and French (1993), we form a factor-mimicking portfolio that essentially goes long on low accruals firms and short on high accruals firms (Conservative Minus Aggressive, or CMA). Since the portfolio is constructed based upon the return-predicting characteristic itself, it is thereby designed to capture any risk factors that may underly the accrual effect even if the relevant risk factors are not observed directly. The empirical results show that partially, CMA has significant positive (negative) influence on stock portfolio with low (high) level accrual, both for single, two, and three factor models, especially at size-accrual category. Other empiric result addition CMA, indicate increasing explanatory power of model in explaining the variation of expected return of stock portfolio on various asset pricing model. Hereinafter three tools of evaluation measurement result indicate that size, book-to-market ratio yet still not shown optimal performance, even after conducted by extension of all model by adding accrual information factors.